2018
DOI: 10.1080/21691401.2018.1476374
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects include antioxidant and pro-oxidation of ascorbic acid on the redox properties of bovine hemoglobin

Abstract: The oxidation reactions have become the main obstacle of development of bovine hemoglobin-derivates products. Herein, the effects of vitamin C (Vc), a easily available natural antioxidant reagent, on the redox reaction of bovine hemoglobin were systematically investigated through methemoglobin (MetHb) formation and spectrophotometric analysis and oxygen affinity monitoring of hemoglobin. The results showed that Vc presented antioxidant effects in the initial stage of reaction and then could accelerated the Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…During the reaction process, ascorbic acid generates hydrogen peroxide under the mediation of oxygen or oxygenated hemoglobin. With the consumption of ascorbic acid, its own scavenging ability cannot balance the accumulated hydrogen peroxide, which leads to the formation of bilirubin and accelerates the oxidation of hemoglobin [ 36 ]. Studies have shown that ascorbic acid will transform from an antioxidant under physiological conditions to a pro-oxidant at higher concentrations.…”
Section: Bioactivity Of Ascorbic Acidmentioning
confidence: 99%
“…During the reaction process, ascorbic acid generates hydrogen peroxide under the mediation of oxygen or oxygenated hemoglobin. With the consumption of ascorbic acid, its own scavenging ability cannot balance the accumulated hydrogen peroxide, which leads to the formation of bilirubin and accelerates the oxidation of hemoglobin [ 36 ]. Studies have shown that ascorbic acid will transform from an antioxidant under physiological conditions to a pro-oxidant at higher concentrations.…”
Section: Bioactivity Of Ascorbic Acidmentioning
confidence: 99%
“…Autoxidation of ferrous HbO 2 to form ferric metHb and superoxide is inevitable. For all the HBOCs, it is important to consider the effect of autoxidation and how to prevent or retard it during the storage and after intravenous administration [9,10,[20][21][22]. In this report, we aimed to investigate the ability of MB to regulate the metHb level of HbV in rats when the rats were resuscitated with HbV suspended in HSA.…”
Section: Discussionmentioning
confidence: 99%
“…The high barrier function of liposomal lipid membrane is important to shield the escape of Hb and its degraded materials when exposed to excess amount of hydrogen peroxide [8]. However, because of such high barrier function without any ionophore, metHb in HbV cannot be reduced by plasma ascorbic acid [9]. Accordingly, we have struggled to establish a metHb reduction system in HbV for a long time [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various redox modifiers (at 1 mmol/L) on calcium uptake were tested, including: ascorbate (Vergauwen et al. ; Chen and Chang ), GSH and GSSG (Jessop and Bulleid ; Saaranen et al. ; Foyer and Noctor ), dehydroascorbate (DHA) (Csala et al.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, if ATP is omitted there was no microsomal calcium uptake. The effect of various redox modifiers (at 1 mmol/L) on calcium uptake were tested, including: ascorbate (Vergauwen et al 2015;Chen and Chang 2018), GSH and GSSG (Jessop and Bulleid 2004;Saaranen et al 2010;Foyer and Noctor 2011), dehydroascorbate (DHA) (Csala et al 1999;Saaranen et al 2010;Foyer and Noctor 2011), H 2 O 2 (Xu et al 1997;Csala et al 1999), and dithiothreitol (DTT) (Ushioda et al 2016).…”
Section: Calcium Uptakementioning
confidence: 99%